CLINICAL CHARACTERISTICS AND ANTIBIOTIC RESISTANCE PHENOTYPES OF KLEBSIELLA PNEUMONIAE ISOLATED AT XUYEN A GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the clinical characteristics and antibiotic resistance phenotypes of Klebsiella pneumoniae isolated at Xuyen A General Hospital, Ho Chi Minh city, period January-June 2025.Methods: A cross-sectional descriptive study was conducted on 50 non-duplicate K.pneumoniae isolates from clinical specimens. Identification was performed using biochemical methods on the VITEK 2 Compact system, with molecular confirmation by real-time PCR using the ZKIR primer pair. Antimicrobial susceptibility testing was performed by automated broth microdilution and interpreted according to CLSI M100 Ed.35 (2025).Results: The mean patient age was 62.7 ± 12.6 years, with equal sex distribution. The most common comorbidities were hypertension (58%) and diabetes mellitus (54%). Urine was the predominant specimen type (44%), and 86% of isolates were community-acquired. All isolates (100%) were resistant to Ampicillin. Carbapenem resistance was detected in 48% of isolates; multidrug resistance (MDR) in 68%; extensive drug resistance (XDR) in 54%; and ESBL production in 18%. Gentamicin was the only antibiotic retaining a high susceptibility rate (74%).Conclusion: K.pneumoniae isolates at Xuyen A General Hospital showed alarming rates of Carbapenem resistance and multidrug resistance. These findings provide the first local microbiological data to support empirical antibiotic therapy at this institution.
Keywords: Klebsiella pneumoniae, Carbapenem resistance, multidrug resistance, resistance phenotype.